Association Between Helicobacter pylori Infection and Short-segment/Long-segment Barrett's Esophagus in a Japanese Population: A Large Cross-Sectional Study. Issue 5 (May 2020) - Usui, Genki; Sato, Hajime; Shinozaki, Tomohiro; Jinno, Toyohisa; Fujibayashi, Kazutoshi; Ishii, Ken; Horiuchi, Hajime; Morikawa, Teppei; Gunji, Toshiaki; Matsuhashi, Nobuyuki
Abstract : Goal: The goal of this study was to investigate the relationship between Helicobacter pylori (H. pylori) infection and short-segment and long-segment Barrett's esophagus (SSBE and LSBE). Background: H. pylori infection is reported to be inversely associated with Barrett's esophagus (BE) in western countries. However, the impact of BE segment length on the association between BE and H. pylori infection has scarcely been investigated. Materials and Methods: The study subjects were 41, 065 asymptomatic Japanese individuals who took medical surveys between October 2010 and September 2017. Using this large database of healthy Japanese subjects, we investigated the association between H. pylori infection and SSBE/LSBE. We used multivariable logistic regression analysis to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: Among the study subjects, 36, 615 were eligible for the analysis. H. pylori seropositivity was significantly associated with a lower rate of LSBE (OR: 0.42; 95% CI: 0.16-0.91) and a higher rate of SSBE (OR: 1.66; 95% CI: 1.56-1.78) after multivariate adjustment. In the subgroup analysis, H. pylori seropositivity was significantly associated with a high rate of SSBE in subjects without reflux esophagitis (RE) (OR: 1.73; 95% CI: 1.61-1.85). However, H. pylori seropositivity was not associated with SSBE in subjects with RE (OR: 1.07; 95% CI: 0.84-1.37). Conclusion: In a Japanese population, H. pylori infection was inversely associated with LSBE but significantly associated with SSBE only in subjects without RE. H. pylori may be a risk factor for SSBE, especially in individuals without RE.